Determining the crystal-field ground state in rare earth heavy fermion materials using soft-X-ray absorption spectroscopy - Hansmann, Philipp; Severing, A.; Hu, Zhiwei; Haverkort, M. W.; Chang, C. F.; Klein, S.; Tanaka, Arata; Hsieh, H. H.; Lin, H. -J.; Chen, C. T.; Fak, B.; Lejay, P.; et al. (Physical Review Letters, 2008)
We infer that soft-x-ray absorption spectroscopy is a versatile method for the determination of the crystal-field ground state symmetry of rare earth heavy fermion systems, complementing neutron scattering. Using realistic and universal parameters, we provide a theoretical mapping between the polarization dependence of Ce M-4,M-5 spectra and the charge distribution of the Ce 4f states. The experimental resolution can be orders of magnitude larger than the 4f crystal-field splitting itself. To demonstrate the experimental feasibility of the method, we investigated CePd2Si2, thereby settling an existing disagreement about its crystal-field ground state.
CRIS-Team WoS Importer:2020-02-19